2010
DOI: 10.1606/1044-3894.4043
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Psychosocial Stressors on the Mental Health Status of African American Caregivers of the Elderly

Abstract: Previous studies focused on African American caregivers of the elderly indicated that they experience less caregiver burden, stress, and strain than caregivers of other ethnic groups. But newer studies point to the stress, strain, burden, and depression among contemporary African American caregivers. A review of the literature reveals three key stressors: limited economic resources, multiple caregiving roles, and dwindling social support. These stressors appear to affect the mental health status and well-being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…It is important to note in light of these caregivers’ struggle to adapt to the disease-related changes in the persons with dementia that previous studies with African-American caregivers have consistently found that they report lower burden than other race/ethnic groups (Bekhet, 2015; Skarupski et al., 2009). This has been challenged as a simplistic and stereotypical view of African-Americans’ experiences with caregiving that does not capture their full experience (Dilworth-Anderson et al., 2002; Fox, Hinton, & Levkoff, 1999; Kingsberry, Saunders, & Richardson, 2010). It is possible that the degree to which burden has been associated with caregiving overall has been more broadly over-estimated than has been generally accepted in the caregiving literature, perhaps in part due to an overreliance on convenience or purposive sampling rather than on probabilistic sampling methods (R. M. Brown & Brown, 2014; Pruchno et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note in light of these caregivers’ struggle to adapt to the disease-related changes in the persons with dementia that previous studies with African-American caregivers have consistently found that they report lower burden than other race/ethnic groups (Bekhet, 2015; Skarupski et al., 2009). This has been challenged as a simplistic and stereotypical view of African-Americans’ experiences with caregiving that does not capture their full experience (Dilworth-Anderson et al., 2002; Fox, Hinton, & Levkoff, 1999; Kingsberry, Saunders, & Richardson, 2010). It is possible that the degree to which burden has been associated with caregiving overall has been more broadly over-estimated than has been generally accepted in the caregiving literature, perhaps in part due to an overreliance on convenience or purposive sampling rather than on probabilistic sampling methods (R. M. Brown & Brown, 2014; Pruchno et al., 2008).…”
Section: Discussionmentioning
confidence: 99%